2009
DOI: 10.1073/pnas.0808581106
|View full text |Cite
|
Sign up to set email alerts
|

Local conformational dynamics in α-helices measured by fast triplet transfer

Abstract: Coupling fast triplet-triplet energy transfer (TTET) between xanthone and naphthylalanine to the helix-coil equilibrium in alanine-based peptides allowed the observation of local equilibrium fluctuations in ␣-helices on the nanoseconds to microseconds time scale. The experiments revealed faster helix unfolding in the terminal regions compared with the central parts of the helix with time constants varying from 250 ns to 1.4 s at 5°C. Local helix formation occurs with a time constant of Ϸ400 ns, independent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
85
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 48 publications
16
85
0
Order By: Relevance
“…The results revealed a position-independent helix elongation time constant (1/k f ) of about 400 ns at 5°C and a position-dependent helix unfolding rate constant (1/k u ) with faster unfolding at the termini (1/k u = 250 ns) compared with the center (1/k u = 1.4 μs). This behavior could be reproduced in simulations using a kinetic version of the linear Ising model (10,11), which suggested that helix elongation and unfolding mainly occur via a diffusing boundary mechanism (i.e., by the movement of the helix/coil boundary along the polypeptide chain). Helix nucleation in a completely unfolded chain and coil nucleation within a helical region are rare events in short model helices (10).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The results revealed a position-independent helix elongation time constant (1/k f ) of about 400 ns at 5°C and a position-dependent helix unfolding rate constant (1/k u ) with faster unfolding at the termini (1/k u = 250 ns) compared with the center (1/k u = 1.4 μs). This behavior could be reproduced in simulations using a kinetic version of the linear Ising model (10,11), which suggested that helix elongation and unfolding mainly occur via a diffusing boundary mechanism (i.e., by the movement of the helix/coil boundary along the polypeptide chain). Helix nucleation in a completely unfolded chain and coil nucleation within a helical region are rare events in short model helices (10).…”
mentioning
confidence: 99%
“…This behavior could be reproduced in simulations using a kinetic version of the linear Ising model (10,11), which suggested that helix elongation and unfolding mainly occur via a diffusing boundary mechanism (i.e., by the movement of the helix/coil boundary along the polypeptide chain). Helix nucleation in a completely unfolded chain and coil nucleation within a helical region are rare events in short model helices (10). The helix/coil boundary is statistically more likely located near the peptide ends than near the center (6,10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1-5). The idea of determining the kinetics of fast processes, other than intramolecular contact formation, by monitoring triplet-state populations was first applied to the helix-coil transition by Lapidus et al (35) and to protein folding by Buscaglia et al (38) using intrinsic probes (tryptophan and cysteine), and has subsequently been used by Kiefhaber and coworkers using extrinsic probes (xanthone and naphthylalanine) to further investigate the helix-coil transition (41), as well as submicrosecond processes in the folding of the villin subdomain (42).…”
mentioning
confidence: 99%